Genomic and phenotypic profiles of two Brazilian breast cancer cell lines derived from primary human tumors - Correa, Natássia C.R.; Kuasne, Hellen; Faria, Jerusa A. Q. A.; Seixas, Cica C. S.; Santos, Iria G. D.; Abreu, Francine B.; Nonogaki, Suely; Rocha, Rafael M.; Silva, Gerluza Aparecida Borges; Gobbi, Helenice; Rogatto, Silvia Regina [UNESP]; Goes, Alfredo M.; et al. (Spandidos Publications, 2013)
Breast cancer is the most common type of cancer among women worldwide. Research using breast cancer cell lines derived from primary tumors may provide valuable additional knowledge regarding this type of cancer. Therefore, the aim of this study was to investigate the phenotypic profiles of MACL-1 and MGSO-3, the only Brazilian breast cancer cell lines available for comparative studies. We evaluated the presence of hormone receptors, proliferation, differentiation and stem cell markers, using immunohistochemical staining of the primary tumor, cultured cells and xenografts implanted in immunodeficient mice. We also investigated the ability of the cell lines to form colonies and copy number alterations by array comparative genomic hybridization. Histopathological analysis showed that the invasive primary tumor from which the MACL-1 cell line was derived, was a luminal A subtype carcinoma, while the ductal carcinoma in situ (DCIS) that gave rise to the MGSO-3 cell line was a HER2 subtype tumor, both showing different proliferation levels. The cell lines and the tumor xenografts in mice preserved their high proliferative potential, but did not maintain the expression of the other markers assessed. This shift in expression may be due to the selection of an 'establishment' phenotype in vitro. Whole-genome DNA evaluation showed a large amount of copy number alterations (CNAs) in the two cell lines. These findings render MACL-1 and MGSO-3 the first characterized Brazilian breast cancer cell lines to be potentially used for comparative research. © 2013 Spandidos Publications Ltd. All rights reserved.
Keywords: Array comparative genomic hybridization; Breast cancer; Cell line; Immunohistochemistry; Primary tumor; Tumor xenograft; agar; cell marker; epidermal growth factor receptor 2; genomic DNA; glyceraldehyde 3 phosphate dehydrogenase; hormone receptor; mucin 1; telomerase; animal tissue; breast cancer; cancer cell culture; cell differentiation; cell proliferation; comparative genomic hybridization; comparative study; controlled study; copy number variation; genomics; histopathology; human; human cell; immunohistochemistry; intraductal carcinoma; MACL 1 cell; MGSO 3 cell; mouse; nonhuman; phenotype; primary tumor; priority journal; stem cell; tumor cells and cell lines; tumor xenograft; Animals; Brazil; Breast Neoplasms; Cell Line, Tumor; Cell Proliferation; Comparative Genomic Hybridization; Female; Humans; Mice; Receptor, erbB-2; Xenograft Model Antitumor Assays